FRI0715 Being a woman and having knee osteoarthritis increases the likelihood of comorbidities. (15th June 2017) - Barbero, M Herrero; Gimenez, S; Vergara, J; Viles, E I Lladό; Martinez, H; Roca, G Rodríguez; Sánchez, L; Díaz, JA Muñoz; Frias, JF; Castaño, A; Jiménez, JJ Díaz; Rodríguez, Ά de Cossío; et al.
Abstract : Background: Osteoarthritis (OA) is the most prevalent joint disease and the leading cause of disability from 60 years onwards. In fact, 14, 8% of the Spanish population has OA. Objectives: This study aimed to determine if there is a differential profile and greater comorbidity in women affected by symptomatic knee OA compared to a control group without OA. Methods: The EMARTRO study was designed as an observational, multicenter, transversal study to compare probability of suffering a comorbidities based on presence of symptomatic knee OA visited by GPs. Sociodemographic, anthropometric, clinical parameters and clinical variables of interest were recorded. The probability of suffering comorbidities in each study group was estimated using the Odds Ratio estimation with conditioned logistic regression models. The HAD scale, the Goldberg health questionnaire were administered to patients and the concomitant medication was also registered. The comparison between groups was done using t-Student, Chi-square and Mann-Whitney. Results: A total of 897 women were included with a mean (SD) age of 67.4 (6.8) years. Osteoarthritic women were obese and had a higher BMI compared with control group, 31.2 (5.5) vs 27.5 (4.3) (p<0.0001), respectively. Regarding blood pressure, no differences were found in the systolic BP (p=0.0646) but in the diastolic, women with OA also had higher values, 77.9 (9.1) vs 75.8 (8.9) mmHg (p=0.0005). In general terms, the presence of OA doubled the probability of having concomitant conditions with respect to controls [OR=2, 220 (95% CI: 1, 449–3, 400) p=0, 0002]. Likewise, women with syntomatic knee OA were more likely to have hypertension [OR=1.697 (95% CI 1.299–2.217), p=0.0001], venous peripheral vascular disease [OR=2.148 (95% CI 1.547–2.984), p<0.0001] and gastroesophageal reflux (OR=1.890 (95% CI 1.297–2.754), p=0.0009). Regarding the mental health of the patients, according to the Goldberg scale, 41% of the patients with OA elicited psychopathology vs 17.8% in controls, p<0.0001. As for the HAD scale, there were more cases of anxiety (p<0.0001) and depression in the OA women (p<0.0001). The greater burden of physical and mental comorbidity in the OA patients was accompanied by a higher consumption of concomitant medications (p<0.0001). Conclusions: The results of the present study indicate that in patients with knee OA, being female is a risk factor for the development of concomitant pathologies. Also, the increased likelihood of suffering from hypertension, venous peripheral vascular disease and gastroesophageal reflux should determine chronic medications for the treatment of osteoarthritis. Disclosure of Interest: None declared